Characteristic of gelatin bone tilapia (Oreochromis nilaticus) extracted with acid and base - Diharmi, Andarini; Nurhanif, Helmi; Sari, N Ira (Acta Aquatica: Aquatic Sciences Journal, 2022)
This study was aimed to determine chemical and physical characteristics of extracted tilapia fish bone gelatin using acid (HCl) and alkaline (NaOH) solutions. The research method was used comparative experimental with Paired t-test consisting of 2 treatments, namely 4% HCl and 4% NaOH with 3 replications. Analysis parameters was consisted of yield, gel strength, viscosity, pH, moisture content, and ash. Characteristics of gelatin extracted using acid solution was resulted in yield, gel strength and viscosity was 4.40, 182.65 g/bloom. and 9.90 cP. Characteristic of gelatin extracted with acid has moisture, ash and pH levels of 5.85%, 2.35%, and 4.25. Gelatin extracted with bases was produced physical characteristics of yield, gel strength, and viscosity of 4.67%, 150.41 g/bloom and 6.03 cP and chemical characteristics (moisture, ash, and pH) were 5.77%, 3.37%, and 10.24. The extraction process using acids and bases resulted in tilapia fish bone gelatin with significantly different characteristics on gel strength, viscosity, pH, and ash except yield and moisture content. Gelatin was produced from tilapia fish bones using acids has gel strength, pH, ash, and moisture content in accordance with SNI standards except for viscosity, while gelatin uses bases had gel strength, viscosity and moisture content, except for pH and ash.Keywords: characteristic physico-chemical; gel strength; pH; viscosity; yield